STUDY OF AERODYNAMIC CHARACTERISTICS OF COTTON FIBER IN SEPARATOR OF PNEUMO-MECHANICAL SPINNING MACHINE - korabayev, sherzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. In this article, the movement of fibers in the air channel and the rotor in the pneumomechanical spinning machine was studied. In the experimental work, the uniformity and stability of the velocity field of each channel for moving fibers in an aerodynamic device were checked. In this case, the airflow speed was changed from 5 m/s to 30 m/s. Differential equations of motion along the OX and OY axis were created taking into account the air resistance. Methods. When determining the movement of fibers in a conical channel, the total speed was divided into components, constant values were found, and general equations of motion were derived. Also, time-dependent graphs of the movement of fibers in a conical channel along the OX axis on different surfaces, and time-dependent graphs of the movement along the OX axis at different speeds were obtained. Results. The results of the research showed that the time-dependent graphs of the movement of fibers along the OX axis in the conical channel on different surfaces, and the time-dependent graphs of the speed s in the channel were obtained. Conclusion. The results of the study showed that when the time-dependent graph of the movement of the fibers in the conical channel along the OX axis on different surfaces S1=14,51, S2=12,56, S3=10,75 was obtained, the fibers on the small surface were straight. When the flow rate is high, a good result was obtained at high speed when the time-dependent graph of the speed of 30m/s 25m/s 20 m/s was obtained in the channel. Keywords: pneumomechanical spinning, separator, air channel, fiber, chamber, cone.